The Compositional and Functional Attributes of Commercial Flours from Tropical Fruits (Breadfruit and Banana) - Shiqi Huang (Foods, 2019)
The objective of this study was to compare the compositional and functional properties of tropical flour sources (two breadfruit flours (type A and type B) and a banana flour) with a more traditional flour source (wheat flour). Macro-nutrient composition, pH, water and oil holding capacity, bulk density, particle size, solubility, swelling power, pasting properties, and thermodynamics (gelatinization and retrogradation) were determined. All flours evaluated were similar in their composition with high levels of carbohydrates (greater than 82.52 g/100 g on a dry-matter basis), with most of the carbohydrate content comprised of starch (greater than 67.02 g/100 g). The tropical fruit flours had greater (p < 0.05) water holding capacity than wheat flour. Breadfruit flour B had the lowest (p < 0.05) bulk density, while banana flour had the greatest (p < 0.05) bulk density. The swelling power of the tropical flours was greater (p < 0.05) than the wheat flour. The viscosity of the tropical flours was higher than wheat flour but decreased significantly when temperature was held at 130 °C. These results indicated that the two breadfruit flours and banana flour have great potential for application in processed food products, and have similar compositional attributes to a more traditional flour.